2021
DOI: 10.3390/ijerph18136947
|View full text |Cite
|
Sign up to set email alerts
|

Taking Students on a Strengths Safari: A Multidimensional Pilot Study of School-Based Wellbeing for Young Neurodiverse Children

Abstract: There is a robust body of psychological research linking youth mental health and academic achievement. However, students in early childhood are rarely represented in this research, and children with disabilities and/or neurological differences are virtually absent. Thus, the present pilot study explored the effects of a structured psychoeducation program designed to enhance school-based wellbeing (SBWB) for young students who are neurodivergent (ND). This study utilized a quasi-experimental design to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 69 publications
0
5
1
Order By: Relevance
“…Analyses of these data from the pilot study provide promising, preliminary support about durable increases in positive affect and covitality, with moderate to large effect sizes (Cohen's d). This is different from previous studies [33,35]. Ana Martínez-Martínez's study showed that after the implementation of the intervention, the reduction effect of bullying behavior was decreased, while the social and emotional ability did not change significantly [35].…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Analyses of these data from the pilot study provide promising, preliminary support about durable increases in positive affect and covitality, with moderate to large effect sizes (Cohen's d). This is different from previous studies [33,35]. Ana Martínez-Martínez's study showed that after the implementation of the intervention, the reduction effect of bullying behavior was decreased, while the social and emotional ability did not change significantly [35].…”
Section: Discussioncontrasting
confidence: 64%
“…A review of the previous literature found that the results provided by previous interventions were not particularly optimistic. Although not statistically significant, the covitality score increased over time, suggesting that they have practical significance in promoting effective social interventions and assessments in the real world [33][34][35]. In addition, the main problems encountered in the effectiveness of these programs have been related to their implementation.…”
Section: Effectiveness Of Covitality Intervention Programsmentioning
confidence: 99%
“…This 20‐item instrument measures students' school‐related gratitude, optimism, zest and persistence, as well as self‐reported prosocial behaviours. Although the SEHS‐P was initially validated with older elementary students (mean age = 11.1 years) (Furlong et al, 2013), Bates and Boren (2019) suggest the SEHS‐P may be appropriate for use with younger children and it has been used reliably with children as young as 8 years old (Wilkins et al, 2015) and in modified format with children as young as 6 years old (Naples & Tuckwiller, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The zest subscale (4 items) measures students' excitement about school (e.g., ‘I get really excited when I learn new things at school’), and the persistence subscale (4 items) measures students' perceived task performance in school (e.g., ‘I keep working until I get my schoolwork right’). The SEHS‐P (Furlong et al, 2013) has established good internal reliability across for full scale covitality (α = .89) and across subscales: school gratitude (α = .71), student zest (α = .78), school optimism (α = .71), student persistence (α = .80) for students in Grades 4–8 (Furlong et al, 2013; Renshaw, 2017; Wang et al, 2018) and with younger students in selected studies (Naples, 2019; Naples & Tuckwiller, 2021; Wilkins et al, 2015). Higher scores reflect higher levels of covitality.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation